2014 36th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2014
DOI: 10.1109/embc.2014.6943913
|View full text |Cite
|
Sign up to set email alerts
|

Design and characterization of a biologically inspired quasi-passive prosthetic ankle-foot

Abstract: By design, commonly worn energy storage and release (ESR) prosthetic feet cannot provide biologically realistic ankle joint torque and angle profiles during walking. Additionally, their anthropomorphic, cantilever architecture causes their mechanical stiffness to decrease throughout the stance phase of walking, opposing the known trend of the biological ankle. In this study, the design of a quasi-passive pneumatic ankle-foot prosthesis is detailed that is able to replicate the biological ankle's torque and ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Another minimally powered foot prosthesis has been designed by Mooney et al [27]. The device uses a pneumatic piston as well as a bending spring in an attempt to closely mimic the stiffness of the biological ankle.…”
Section: Untethered Ankle Devicesmentioning
confidence: 99%
“…Another minimally powered foot prosthesis has been designed by Mooney et al [27]. The device uses a pneumatic piston as well as a bending spring in an attempt to closely mimic the stiffness of the biological ankle.…”
Section: Untethered Ankle Devicesmentioning
confidence: 99%
“…In the same vein as Brackx et al 5 Mooney and his team found that the existing prosthetic ankles at their time were incapable of providing the amputee with "biologically realistic" ankle torque and angles. 7 They developed a quasi-passive ankle with pneumatic components. They compared their ankle with a passive ESR prosthetic foot.…”
Section: Survey Passive Lower Limb Prosthesesmentioning
confidence: 99%
“…All the test data was compared to the prosthesis that the test subjects used daily. Nickel et al 7 outlined user experience while wearing the prosthesis. The experimental data is shown in Figure 3 that compares kinematic and kinetic data from their prototype and the subject's prosthesis.…”
Section: Survey Passive Lower Limb Prosthesesmentioning
confidence: 99%
See 2 more Smart Citations